Improving the Ability to Recognize Consonants Through Smart Box Media for Children aged 4-5 Years in Kindergarten: Peningkatan Kemampuan Mengenal Huruf Konsonan Melalui Media Kotak Pintar Anak Usia 4-5 Tahun Di Taman Kanak-kanak - Nada Bela Untari; Choirun Nisak Aulina (Academia Open, 2021)
The ability to recognize consonants has an important role in the lives of early childhood because introducing consonants to children is the first step for children to be able to read and to make a word, consonants and vowels are needed. This study aims to determine the application and results of the "Smart Box" media towards increasing consonant recognition in children in group A. This study uses Classroom Action Research as an approach to improve children's ability to recognize consonants. It is carried out in 2 cycles which are divided into three stages, namely pre-cycle, cycle I and cycle II to obtain the expected results. In the pre-cycle the result of the percentage of action achievement value was 46.16%, while in the first cycle the percentage increased by 22.09% so that the percentage score was 69%, which means it was not successful. Then the researcher continued by giving action in the second cycle, after doing the research in the second cycle, the percentage of action achievement value became 88.58%%, so that the percentage value obtained in the first cycle and second cycle increased by 19.58%. With this it can be seen from the comparison between cycles I and II during the research. From the results obtained, there is an increase which proves that using the "Smart Box" media can improve the ability to recognize children's consonants.